As imagens projetadas pelo computador como facilitadoras do ensino/aprendizagem: uma análise do ensino nas escolas municipais de Amélia Rodrigues-BA - Brandão Neto, Moysés Lopes (2014)
This is a study of exploratory and qualitative approach, which aims to realize the extent to which computer use may influence the teaching in schools of Amelia Rodrigues - BA, through the images projected by this. To achieve this goal, a survey was conducted with the intention of understanding the influence of modern tools in the teaching / learning process, and aspects that contribute to improve it, awakening in students and teachers interest in learning about the cultural change for this to be perceived by students as something pleasurable and not just an obligation. It is believed that the use of the omputer is a possible alternative for improving the education of contemporary society , breaking barriers between the culture of the twentieth century teaching and learning that brings a new methodology that appropriates the technological advances , and aims to become the new culture of teaching . The search for theoretical information was held in the national literature in online publications in the SciELO database and Google Scholar, books and journals in the area of education were also analyzed. The content covered by this work , we try to explain the possible improvement of learning with the use of computers and educational software , showing that the use of new technologies makes the most dynamic and fun for those who learn and easier lesson for those who submit teaches. The results showed that it is possible to improve the conditions of teaching with computer use, and that students are willing to be involved with new knowledge when presented in a pleasant way. We also observed the lack of human , financial and material for deployment of IT equipment provided by government programs , and lack of political will to change this picture features. The change in these factors and breaking of paradigms is possible with effective action, involving government, education professionals, educational institutions and the participation of society, breaking the barriers that prevent the proper use of public property for the sake of a better future for good common. The results showed that the lack of interest by government projects into practice has a strong link with the political will of government agencies, which is a serious problem in developing countries, lacking in social actions, and policies and legal guarantees promote cultural and quality of life for its citizen’s changes.